The Importance of Literature in Modern Society (Eurasian Journal of Learning and Academic Teaching, 2022)
The article deals with literature as an important science in linguistics. For the majority of people around the world, our first serious encounter with literature comes from school. Reading and writing has been drilled in all of us from an early age and this is set in motion with the start of examinations.